THE USE OF UN/MARKED CODE TO SHOW POLITENESS AMONG MULTILINGUAL CUSTOMERS - Putri Nur Hidayah (University of Muhammadiyah Malang, 2021)
The use of un/marked codes in expressing dissatisfaction has become a typical case among Indonesian multilingual customers which show various ways to convey dissatisfaction. This study applies theories of politeness strategy, politeness principles, and three types of complaining responses. These theories are applied to analyse marked and unmarked complaints in Indonesian and English. It attempts to show how customers express their complaints by using specific codes implying im/politeness, finding the underlying reasons by choosing certain codes, and categorizing the complaints based on three types of complaining responses. The data is taken from observation in a Japanese restaurant in form of conversation, both in Indonesian and English. The results show that the unmarked complaints are attempted to get a response and the marked complaints to exclude the waitress. The unmarked and marked complaints apply underlying reasons as assertive and impositive uses, but the politeness principle here is used to decrease the impositive by using interrogative sentences and marked code. The unmarked code is an action of voice response to get a response from the restaurant parties. It also found that the younger multilingual customers tend to use a private response, whereas the adult customers use a voice response.